Type-Specific Persistence/Clearance Results in Human Papillomavirus Infections in Turkish Women - Haci Ozturk Sahin; Beril Gurlek; Bulent Demir; Fatma Silan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The persistence of high-risk human papillomavirus infections, most of which are known to be transient is of critical importance for the development of precursor lesions and cancer in the cervix. The aim of the present study is to investigate the persistence and clearance of genotype-based human papillomavirus infections and also some cofactors that could be effective in persistence.